Superior frontal sulcus: a non-eloquent corridor for cavernomas of the internal capsule - Pereira, Felipe Salvagni; Jiménez, Luis Ángel Canache; Aguaisa, Edgar David Tenelema; Apaza-Tintaya, Rene Alejandro; Biondi-Soares, Luis Gustavo; Paitán, Alexander Feliciano Vilcahuamán; Soto, Pedro Henrique Teixeira; Wuo-Silva, Raphael; Chaddad-Neto, Feres (Frontiers in Neurology, 2024)
Deep cavernomas of eloquent areas, located in the region of the basal nuclei and thalamus, account for 9 to 36% of these encephalic vascular malformations. Internal capsule cavernomas are particularly challenging, as they are surrounded by important projection fibers and their manipulation can lead to permanent deficits. To demonstrate through surgical cases that cavernomas of the internal capsule can be approached by frontal craniotomy, via the superior frontal sulcus, in a curative manner and with low morbidity. We presented two cases of cavernomas of the internal capsule operated, whose treatment was microsurgical resection via frontal craniotomy and access to the lesion via the superior frontal sulcus, described step-by-step. To elucidate the rationale behind the decision, we used preoperative images with an emphasis on the patients' tractography and the importance of comparing these images with anatomical specimens dissected in the neuroanatomy and microsurgery laboratory. The two cases of internal capsule cavernomas, one in the anterior limb and the other in the posterior limb, were treated surgically via the superior frontal sulcus. Both patients showed radiological cure and clinical improvement in the post-operative segment. The patient consented to the procedure and to the publication of his/her image. Treatment of internal capsule cavernomas via the superior frontal sulcus has proven to be a safe and effective option.